Nutrient content and seasonal fluctuations in the leaf component of coark-oak (Quercus suber L.) litterfall (Plant Ecology, 1996)
Nutrient content and seasonality of the leaf component in cork-oak litterfal were studied over a two year period in two cork-oak forest sites differing in biomass and edaphic condition in the north-eastern Iberian peninsula. Fallen senescent leaves compared to young leaves showed higher non-mobile nutrient concentrations and lower mobile nutrient concentrations, specially P, N, K, and Mg. At both sites, seasonal fluctuations affected both leaf production and leaf mineral content. The maximum leaf fall period correspond to the start of the vegetative growth and to the lowest N and P concentration in the falling leaves. The opposite was true for the winter, when litterfal was minimal and N and P content in falling leaves was at a maximum. The comparison between falling leaves and canopy leaves suggests that the analysis of fallen leaves can be a useful measure of N and P nutrition in cork-oak. We found site dependent differences in nutrient content and nutrient remobilization. In comparison with Q. ilex, although litter production was in the same range, nutrient retranslocation was greater for Q. suber.